Total Physical Response (TPR) and English language vocabulary among middle basic education students at an educative institution in Loja, school year 2023-2024 - Jara Ordoñez, Cecilia Elizabeth (2025)
Vocabulary is an essential component in learning a language, as it facilitates effective communication and understanding between speakers, so it is essential to look for strategies to improve it. Consequently, this study aims to improve English language vocabulary among students of a public institution through the implementation of the Total Physical Response (TPR) method. To achieve this goal, a mixed-method approach and an action research study were employed, involving 27 students from a public institution in Loja, Ecuador with an A1.2 level of English over a six-week intervention period. Data collection methods include pre- and post-tests, field notes for observational data, and questionnaires to collect student perceptions. The findings indicate that the integration of Total Physical Response improves vocabulary learning. In terms of its effect, TPR has a positive impact on vocabulary acquisition, since it increases student´s engagement and makes the learning process more dynamic. In exploring students' experiences, the use of TPR in English vocabulary learning was generally very positive and the activities that supported this method were songs, circle games, Simon Says, and Storytelling which contributed to an improvement in sub aspects of vocabulary such as spelling, associations, grammatical functions, and collocations. Therefore, the students show greater motivation, better comprehension and retention of new words. It is recommended to use Total Physical Response in English classes to improve children's educational outcomes. Key Words: TPR activities, young learners, effectiveness of TPR, vocabulary learning